Efficacy and Safety of a Tofacitinib-based Immunosuppressive Regimen After Kidney Transplantation: Results From a Long-term Extension Trial. Issue 9 (September 2018) - Busque, Stephan; Vincenti, Flavio G.; Tedesco Silva, Helio; O'Connell, Philip J.; Yoshida, Atsushi; Friedewald, John J.; Steinberg, Steven M.; Budde, Klemens; Broeders, Emine N.; Kim, Yon Su; Hahn, Carolyn M.; Li, Huihua; et al.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor. This open-label, long-term extension (LTE) study (NCT00658359) evaluated long-term tofacitinib treatment in stable kidney transplant recipients (n = 178) posttransplant. Methods: Patients who completed 12 months of cyclosporine (CsA) or tofacitinib treatment in the phase IIb parent study (NCT00483756) were enrolled into this LTE study, evaluating long-term tofacitinib treatment over months 12 to 72 posttransplant. Patients were analyzed by tofacitinib less-intensive (LI) or more-intensive (MI) regimens received in the parent study. For both groups, tofacitinib dose was reduced from 10 to 5 mg twice daily by 6 months into the LTE. Patients were followed up through month 72 posttransplant, with a focus on month 36 results. Results: Tofacitinib demonstrated similar 36-month patient and graft survival rates to CsA. Biopsy-proven acute rejection rates at month 36 were 11.2% for CsA, versus 10.0% and 7.4% (both P > 0.05) for tofacitinib LI and MI, respectively. Least squares mean estimated glomerular filtration rates were 9 to 15 mL/min per 1.73 m 2 higher for tofacitinib versus CsA at month 36. The proportions of patients with grade 2/3 interstitial fibrosis and tubular atrophy in month 36 protocol biopsies were 20.0% for LI and 18.2% for MI (both P > 0.05) versus 33.3% for CsA. Kaplan-Meier cumulative serious infection rates at month 36 were numerically higher for tofacitinib LI (43.9%; P = 0.45) and significantly higher for MI (55.9%; P < 0.05) versus CsA (37.1%). Conclusions: Long-term tofacitinib continued to be effective in preventing renal allograft acute rejection and preserving renal function. However, long-term tofacitinib and mycophenolic acid product combination was associated with persistent serious infection risk.